Mechanistic Insights into Autophagy-Dependent Cell Death (ADCD): A Novel Avenue for Cancer Therapy - Md Ataur Rahman; Maroua Jalouli; Mohammed Al-Zharani; Ehsanul Hoque Apu; Abdel Halim Harrath (Cells, 2025)
Autophagy-dependent cell death (ADCD) presents a promising but challenging therapeutic strategy in cancer treatment. Autophagy regulates cellular breakdown and stress responses, serving a dual function—either inhibiting tumorigenesis or facilitating the survival of cancer cells in advanced stages. This paradox presents both opportunities and challenges in the exploration of autophagy as a potential target for cancer treatment. In this review, we explore various pharmacological agents, including autophagy inhibitors (e.g., chloroquine, 3-MA) and activators (e.g., rapamycin, metformin), which have demonstrated effectiveness in modulating autophagy-dependent cell death (ADCD). These agents either enhance cancer cell apoptosis or sensitize tumors to conventional therapies. Combination therapies, such as the use of autophagy modulators alongside chemotherapy, immunotherapy, or radiation therapy, offer enhanced therapeutic potential by overcoming drug resistance and improving overall treatment efficacy. Nonetheless, significant challenges remain, including tumor heterogeneity, treatment resistance, and off-target effects of autophagy-targeting agents. Future progress in biomarker discovery, precision medicine, and targeted medication development will be crucial for enhancing ADCD-based methods. Although autophagy-dependent cell death presents significant potential in cancer treatment, additional studies and clinical validation are necessary to confirm its position as a conventional therapeutic approach. Therefore, this review aims to identify the existing restrictions that will facilitate the development of more effective and personalized cancer therapies, hence enhancing patient survival and outcomes.